Site surface conditions effects on the static friction coefficient for metallic materials - Chanchi Golondrino, José Christian; Moreno Castañeda, Brayanath; Restrepo Botero, Mateo (Revista Ingeniería de Construcción, 2023)
A methodology for quantifying the variation of the static friction coefficient µ due to different site surface conditions, and for metallic materials with hardness ratios ρ = 0.5 – 2, is proposed. ρ is defined as the ratio between the material hardness and the A36 steel hardness. For each material, 7 coupons were considered in the site conditions “clean”, “bought”, “polished” and “corroded”. Results show if surfaces are kept as “bought”, µ may increase or decrease up to 20%, if surfaces are polished, µ may increases up to 37%, and if surfaces are corroded µ may increases up to 410% when considering corrosion rates of 90 – 670 µm/year. These increments or reductions were calculated respect to the site condition “clean”. Results also show for “clean” surfaces and for ρ ≤ 1.7, µ is dependent on ρ, for ρ > 1.7, µ is approximately constant. A model for quantifying variations of µ for the considered site surface conditions was proposed.